Green innovation and the development of sustainable communities: The case of Blueprint Regeneration's Trent Basin development. (February 2018) - Rossiter, Will; Smith, David J
With nearly one-third of the UK's total consumption of energy devoted to the domestic household sector, sustainable housing developments have an important part to play in reducing greenhouse gas emissions in order to combat climate change. This study analyses a sustainable housing development in the city of Nottingham in the United Kingdom that takes the form not merely of a sustainable housing project, but rather an experiment in developing sustainable communities. In terms of green or eco-innovation, it incorporates innovations in housing design geared to curbing the demand for energy; technological innovations in energy supply centred on a novel community energy system; and innovations in the governance models employed. The scheme is notable for the novel public–private partnership carrying out the development, which specializes in developments characterized by an emphasis on quality urban design and a strong commitment to environmental sustainability.